The European Union and UN Millennium Development Goals in Nigeria: A Study of the Micro Projects Programmes (MPPs) in the Niger Delta Region - Nnamdi O. Nwaodu (Africa’s Public Service Delivery & Performance Review, 2016)
The present Cotonou Accord was signed by the EU, 77, African Caribbean and Pacific (ACP) countries towards halving poverty as prescribed by the UN Declaration by 2015. The EU's interventionin the rural communities of the oil producing states of Nigeria (Niger Delta) clearly shows her commitment towards the above stated global drive for the eradication of poverty especially in the Third World. Bringing about the establishment of the Micro ProjectProgrammes (MPP3, MPP6 and MPP9) for the nine states of the region between 1999 and 2012 and expended over €210 million on the programmes. Four years after theimplementation of the programmes, arising questions include: to what extent did the EU-MPPs achieve the set goals of poverty reduction in the region? And how sustainable are the achievements of the programmes? Using ex post facto research design, it was found out that amidst numerous challenges the MPPs actually reduced the level of poverty in the region through the provision of over 20,000 micro projects to more than 4000 rural communities in the nine states it covered. It therefore recommended that similar programmes be initiated by all other international development agencies as to speed up the reduction of poverty in the UN targeted areas though behind the originally target period of 2015. The study contends that an effective administrative institutional framework of the EU- MPPs should serve as model to other development agencies not only in Nigeria but across the developing economies of the world.